2019
DOI: 10.1186/s13052-019-0727-6
|View full text |Cite
|
Sign up to set email alerts
|

Report on advances for pediatricians in 2018: allergy, cardiology, critical care, endocrinology, hereditary metabolic diseases, gastroenterology, infectious diseases, neonatology, nutrition, respiratory tract disorders and surgery

Abstract: This review reported notable advances in pediatrics that have been published in 2018. We have highlighted progresses in allergy, cardiology, critical care, endocrinology, hereditary metabolic diseases, gastroenterology, infectious diseases, neonatology, nutrition, respiratory tract disorders and surgery. Many studies have informed on epidemiologic observations. Promising outcomes in prevention, diagnosis and treatment have been reported. We think that advances realized in 2018 can now be utilized to ameliorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 165 publications
(166 reference statements)
0
1
0
Order By: Relevance
“…6 In 2018, Caffarelli et al reported on some of the advances made in PCCM, such as the Paediatric Emergency Care Applied Research Network (PECARN) algorithm in evaluating the need for computed tomography (CT) scanning in children with TBI. 7 With continuing advancements in PCCM and the field's evolution, reliable reporting of these developments remains of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…6 In 2018, Caffarelli et al reported on some of the advances made in PCCM, such as the Paediatric Emergency Care Applied Research Network (PECARN) algorithm in evaluating the need for computed tomography (CT) scanning in children with TBI. 7 With continuing advancements in PCCM and the field's evolution, reliable reporting of these developments remains of utmost importance.…”
Section: Introductionmentioning
confidence: 99%